2019
DOI: 10.2147/ijgm.s215548
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dyslipidemia in diabetes: a population-based study in Bali</p>

Abstract: Purpose To establish the lipid pattern in subjects with diabetes mellitus (DM) and factors that are correlated with insulin resistance and lipid disorders in a population of Bali. Methods A cross-sectional population-based study which enrolled 1840 subjects (age 13–100 years) from 7 villages was carried out. Several clinical parameters were measured including age, gender, body mass index, waist circumference (WC), fasting blood glucose, total cholesterol (TC), triglycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
2
4
1
1
Order By: Relevance
“…The pooled prevalence of high LDL-C was 41.13%, which is akin to an evidence in the United States (53%) [ 66 ]. However, LDL-C in our study is lower than other studies in Thailand (56.54%) [ 28 ], Tanzania (72.3%) [ 57 ], India (57.3%) [ 58 ], Brazil (79%) [ 64 ], Yemen (67.5%) [ 65 ], and Jordan (91.5%) [ 59 ]. The reason for the lower estimated high LDL-C in our review could be due to variations in sample size and scope of the study.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…The pooled prevalence of high LDL-C was 41.13%, which is akin to an evidence in the United States (53%) [ 66 ]. However, LDL-C in our study is lower than other studies in Thailand (56.54%) [ 28 ], Tanzania (72.3%) [ 57 ], India (57.3%) [ 58 ], Brazil (79%) [ 64 ], Yemen (67.5%) [ 65 ], and Jordan (91.5%) [ 59 ]. The reason for the lower estimated high LDL-C in our review could be due to variations in sample size and scope of the study.…”
Section: Discussioncontrasting
confidence: 88%
“…Finally, we estimated the prevalence of abnormally low HDL-C (44.36%) among people living with DM which is in line with other nation-wide studies in Saudi Arabia (40%) [67], Korea (41.2%) [69], and China (40.8%) [68] and local studies in India (35.7%) [58] and Brazil (34.9%) [64]. The estimate of low HDL-C is higher than studies in the United States (23%) [66] and Yemen (25.5%) [65].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Due to westernization and urbanization in the past three decades, the Balinese population has undergone lifestyle changes that raised the prevalence of metabolic syndrome (MetS) and metabolic disorders, such as obesity and diabetes mellitus (DM). These traits are known to be closely associated with dyslipidemia through insulin resistance ( Athyros et al, 2011 ; Suastika et al, 2011 , 2019 ), which also increase the Balinese’s risk for dyslipidemia. A cross-sectional survey study carried out in Bali Island had reported the frequency of dyslipidemia in normal glucose tolerance subject group as follows, high LDL-C (73.8%), high non-HDL-C (53.9%), low HDL-C (31.3%), and high TG (20.4%).…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional survey study carried out in Bali Island had reported the frequency of dyslipidemia in normal glucose tolerance subject group as follows, high LDL-C (73.8%), high non-HDL-C (53.9%), low HDL-C (31.3%), and high TG (20.4%). Meanwhile, both impaired fasting glycemia (IFG) and DM subject groups had relative higher percentage in all parameters, showing a positive correlation between glucose impairment with dyslipidemia ( Suastika et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%